Pengaruh Disiplin Kerja dan Kompensasi Terhadap Kinerja yawan Pada Lembaga Pendidikan Brilliant Education Centre Probolinggo - Junaidi Junaedi; Indah Widia Lestari (Ecobuss, 2017)
From a general overview of the company five years latest, there was find three important issues, namely the discipline of work, compensation, and performance of the employee. The purpose of this research was to examine and analyze the extent of the influence of discipline of work and compensation to the performance of the employee in the Brilliant Education Centre Probolinggp Education Agency as well as to determine which variables are the most dominant influence on the performance of employees. This research used a quantitative research method with the explanatory approach to testing the hypothesis that has been set. The number of samples as many as 20 people by using sampling techniques saturated. Data sources derived from primary data and secondary data. Technics of analysis used analysis techniques of Multiple Linear Regression, validity test and reliability as well as a partial test and simultaneous test with the help of a computer program SPSS 16.0 for windows, which is a statistical computer program capable of processing statistical data. From the F-test, the independent variable of the discipline of work and compensation together or simultaneously significant effect on the dependent variable of the performance of employees in Brilliant Education Centre Probolinggo Education Agency. Thus the first hypothesis in this research was proved. From the result of analysis Multiple Linear Regression, the effect of independent variables of the discipline of work and compensation on the dependent variable of the performance of employee there was a strong and significant influence. Thus the second hypothesis in this research was proved. The most dominant variable effect the performance of employee was the discipline of work, the reason was the discipline of work has a standardized coefficient of the largest value when compared with the variable compensation. Keywords: the discipline of work, compensation, and performance of the employee.